Battle Of Brand Loyalty: Based On Social Media Advertising – Gojek And Grab - Calysta, Netha Eliana; Suade, Yuyun Karystin Meilisa (Value : Jurnal Manajemen dan Akuntansi, 2024)
The use of social media advertising is certainly familiar to consumers as one of the marketing strategies for brands or products in the company. This study will look at the level of consumer loyalty to Gojek and Grab through brand image and brand awareness. This study aims to see between the two brands which brand is superior in using social media advertising in increasing consumer loyalty, namely generation z people in Makassar city, Indonesia. This study uses quantitative methods by analyzing 265 respondents and will be analyzed using PLS-SEM. The results of this study indicate that Gojek is superior in utilizing brand image and brand awareness through social media advertising. This is evidenced by the relationship between social media advertising has no significant effect on brand loyalty. Nevertheless, brand image and brand awareness have a significant positive relationship to brand loyalty. Furthermore, the Grab brand is superior in increasing its brand loyalty through social media advertising, brand image, and brand awareness. In addition, Grab's brand image and brand awareness have a positive significant relationship to brand loyalty.